The Benefit of DLBS1033 for Deep Vein Thrombosis in A Hemorrhagic Stroke Patient: A Case Report - Rizaldy Taslim Pinzon; Ivana Prasetianingtyas (MEDICINUS, 2025)
Background: Deep vein thrombosis (DVT) is a significant complication in patients with hemorrhagic stroke, primarily due to prolonged immobility. Although anticoagulants are routinely used for DVT prophylaxis in stroke patients, its application in hemorrhagic stroke remains controversial due to the increased risk of intracranial bleeding. This resulting in a challengingbalance between preventing DVT and avoiding further hemorrhage. DLBS1033, a bioactive protein fraction from the earthworm Lumbricus rubellus, demonstrated antithrombotic, thrombolytic, and antiplatelet aggregation activities, offeringa potential alternative therapeutic approach in such cases.Case report: A 68-year-old male with history of chronic hypertension and well-controlled type 2 diabetes mellitus presented to the emergency department with drowsiness and left-sided hemiparesis, subsequently diagnosed as intracerebral hemorrhage. On the sixth day of hospitalization, the patient developed DVT. DLBS1033 was administered as part of themanagement strategy.Conclusions: This case report demonstrates the effective and safe use of DLBS1033 in managing DVT for patient with hemorrhagic stroke. DLBS1033 is considered a potential promising agent for treating thrombus-related diseases.